Matrine suppresses the migration and invasion of NSCLC cells by inhibiting PAX2-induced epithelial-mesenchymal transition - Yang J (OncoTargets and Therapy, 2017)
Jun Yang,1,* Du He,2,* Yan Peng,1 Hongzhen Zhong,1 Yuhong Deng,1 Zhonghua Yu,1 Chengnong Guan,1 Yufang Zuo,1 Zumin Xu1 1Cancer Center, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 2Department of Oncology, the Central Hospital of Enshi Autonomous Prefecture, Enshi, China *These authors contributed equally to this work Abstract: Non-small cell lung cancer (NSCLC) is the major cause of deaths among all the cancer types worldwide. Most of the NSCLC is diagnosed at an advanced stage and the 5-year overall survival rate is low. The reason for the low survival rate of patients with NSCLC is mainly due to distant metastasis. Matrine, a traditional Chinese medicine, has been shown a significant anti-proliferation and anti-invasive effect in tumors. However, little is known on the anti-invasive mechanism of matrine in lung cancer. Therefore, we tried to investigate the molecular mechanism of matrine on the invasive ability of NSCLC cells in vitro. Cell Counting Kit-8 assay was used to evaluate the cell viability. Transwell assay was used to detect the migration and invasion abilities. Microarray assay was used to analyze the differentiated expression genes with or without matrine treatment. Western blotting and real-time polymerase chain reaction were applied to detect the expressions of PAX2, E-cadherin and N-cadherin. Our study showed that matrine could suppress the proliferative activity of NSCLC cells in a dose- and time-dependent manner. Further investigation discovered that the migration and invasion of NSCLC cells were significantly inhibited by treatment with different concentrations of matrine. Microarray assay, real-time polymerase chain reaction and western blotting showed that matrine could significantly decrease the expression of PAX2. In addition, epithelial-mesenchymal transition and related proteins were decreased. In conclusion, matrine may block PAX2 expression to interfere with epithelial-mesenchymal transition signaling pathway that ultimately inhibit the migration and invasion of NSCLC cells in vitro. Matrine might serve as a potential agent for NSCLC treatment. Keywords: matrine, PAX2, epithelial-mesenchymal transition, migration, invasion